Flowerlike WSe2 and WS2 microspheres: one-pot synthesis, formation mechanism and application in heavy metal ion sequestration. Issue 24 (2nd March 2016) - Li, Wei; Chen, Dehong; Xia, Fang; Tan, Jeannie Z. Y.; Song, Jingchao; Song, Wei-Guo; Caruso, Rachel A.
Abstract : WSe2 and WS2 microspheres were synthesized by a solvothermal method and demonstrated outstanding uptake capacities for Pb 2+ and Hg 2+ . Abstract : Flowerlike WSe2 and WS2 microspheres were synthesized by a facile and scalable one-pot solvothermal method. Their formation mechanism followed the reaction between dissolved W(CO)6 and dissolved S or melted Se without complete decomposition of W(CO)6 into tungsten. As novel efficient sorbents, WSe2 and WS2 demonstrated outstanding uptake capacities for Pb 2+ and Hg 2+ .